Multilayered Democracy in Papua: A Comparison of "Noken" System and Electoral College System in the United States - Yunus, Ahsan (Hasanuddin Law Review, 2020)
The elucidation of understanding popular sovereignty through the implementation of democratic principles when applied to a pluralistic Indonesian society requires a comprehensive study. This study is a normative-legal research by using statute, case, and conceptual approaches. This paper provides information on the latest trend in research. The results show that the characteristics of the general election by Noken system are in line with the Electoral College system to presidential elections in the United States, especially in the Noken system as represented by the chieftain (election by the big man). The Noken system is the result of the relations of political culture and the strengthening of local democracy. Hence, the constitutionality of Noken system is a translation of the constitution that pays attention to the social diversity that lives in society. Not only in the context of general elections, but in every aspect of national and State life, as more attention is given to the constitution of social diversity in society (constitutional pluralism).